Complete remission after single agent blinatumomab in a patient with pre-B acute lymphoid leukemia relapsed and refractory to three prior regimens: hyperCVAD, high dose cytarabine mitoxantrone and CLAG. Issue 1 (December 2015) - Linder, Katherine; Gandhiraj, Deepthi; Hanmantgad, Madhura; Seiter, Karen; Liu, Delong
Abstract Background The current standard of care for relapsed and refractory acute lymphoblastic leukemia (ALL) is combination chemotherapy. Case presentation We report a case of highly refractory ALL who was treated with blinatumomab. The ALL in this patient relapsed within a month after completion of hyperCVAD regimen and was refractory to high dose mitoxantrone/cytarabine and CLAG regimens. Conclusion This highly refractory pre-B Ph− ALL was induced to complete remission after one course of single agent blinatumomab.